2022
DOI: 10.3390/plants11152037
|View full text |Cite
|
Sign up to set email alerts
|

Enclosure in Combination with Mowing Simultaneously Promoted Grassland Biodiversity and Biomass Productivity

Abstract: Grassland is the primary land use in China, which has experienced extensive degradation in recent decades due to overexploitation. Here, we conducted field experiments to quantify the degraded grassland’s recovery rate in Northeast Inner Mongolia in response to restoration measures, including fallow + enclosure (FE) and mowing + enclosure (ME) in comparison to livestock grazing (LG), since 2005. Plant community properties were surveyed and aboveground biomass (AGB) sampled in summer 2013. Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Moreover, we demonstrate that the diversity-productivity relationship exhibits a downward trend against the increasing LUI gradient as in the order of enclosed grassland, forest understory grassland, wetland grassland, mowing grassland, moderate-grazing grassland, and heavy-grazing grassland that we surveyed ( Figure 6 ), meaning that the diversity-productivity relationship not only changes magnitude but also switches directions under varying levels of LUI. While these findings are in line with some authors for a more complex diversity-productivity relationship ( Levine et al., 2004 ; Hector and Bagchi, 2007 ; Duffy et al., 2017 ), and confirm and extend previous research in the region ( Li et al., 2022 ), these findings challenge the mainstream opinion that supports a consistently positive relationship between plant diversity and productivity ( Isbell et al., 2015 ; Wang et al., 2019 ; Omidipour et al., 2021 ; Thakur et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, we demonstrate that the diversity-productivity relationship exhibits a downward trend against the increasing LUI gradient as in the order of enclosed grassland, forest understory grassland, wetland grassland, mowing grassland, moderate-grazing grassland, and heavy-grazing grassland that we surveyed ( Figure 6 ), meaning that the diversity-productivity relationship not only changes magnitude but also switches directions under varying levels of LUI. While these findings are in line with some authors for a more complex diversity-productivity relationship ( Levine et al., 2004 ; Hector and Bagchi, 2007 ; Duffy et al., 2017 ), and confirm and extend previous research in the region ( Li et al., 2022 ), these findings challenge the mainstream opinion that supports a consistently positive relationship between plant diversity and productivity ( Isbell et al., 2015 ; Wang et al., 2019 ; Omidipour et al., 2021 ; Thakur et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Although we opt for the LUI classes in this paper, other options – e.g., the Integrated Disturbance Index ( Ligeiro et al., 2013 ) – need to be explored; Thirdly, the synergistic diversity-productivity relationship under moderate grazing or mowing management deserves more attention. On the one hand, there is a good chance that the dual goals of grassland utilization and conservation can be simultaneously met under these management schemes ( Tälle et al., 2016 ; Li et al., 2022 ). On the other hand, although previous research suggested that diversity-productivity synergy could be fulfilled via, e.g., competition mediation ( Peintinger and Bergamini, 2006 ; Fagundez, 2016 ) and plant-soil interactions ( Storkey et al., 2015 ; Xu et al., 2022b ), it is still unclear how this synergy can be reliably triggered and temporally sustained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grasslands store approximately one-third of the global terrestrial C. On the one hand, improvements in grazing management and biodiversity restoration have the potential to deliver natural climate benefits in grasslands through soil C sequestration ( Yao et al., 2015 ; Li et al., 2022 ). On the other hand, however, widespread grassland degradation poses significant threats to the soil C pool by enhanced soil C mineralization ( Ye et al., 2010 ; Abdalla et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…All these rates are significantly higher than the 0.4% threshold stipulated by the 4 per Mille Initiative. Under the irrigated conditions, even higher SOC increase rates were projected ( Figure 9 ), reflecting the primary influence of C input quantities – both from the aboveground biomass through the litterfall pathway and from the belowground biomass through the root pathway – on soil C sequestration ( Chen et al., 2021 ; Li et al., 2022 ; Xu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%